The study of analgesic effect of 5-(furan-2-yl, 2-methylfuran-3-yl)-4-amino-1,2,4-triazole-3-thion derivatives - D. M. Danilchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Abstract